How Do Iranian Men Perceive Their Sexual and Reproductive Health Situation? A Qualitative Content Analysis - Razieh Lotfi; Seyed Ali Azin; Effat Hatefnia; Mina Amiri; Masoumeh Simbar; Fahimeh Ramezani Tehrani (Shiraz University of Medical Sciences, 2022)
Background: Males' viewpoint about sexual and reproductive health (SRH) and their situation are essential components of men's and women's health in the community. Men have been overlooked in reproduction health, especially with reproductive issues such as contraception, sexually transmitted infections (STIs), infertility, and sexual function. This study aimed to investigate the males' perceptions of their SRH situation in Iran. Methods: A qualitative study was conducted from May 2016 to April 2017 on data retrieved through semi-structured interviews with 19 adult males aged 18 to 59 years. The participants were purposefully recruited from among populations of health centers in Alborz province, Iran. Conventional content analysis in OneNote software version 2016 was used for data analysis. Results: Three main themes and nine categories emerged including 1) Perceived SRH needs, including "need to increase men's awareness about SRH", "need to have an accessibility to SRH services", and "need to have a high-quality sexual relationship"; 2) perceived SRH responsibilities, including "health-seeking behaviors", "sexual skills", "childbearing responsibilities", and "ethical commitment", and 3) Men' perception of trends of social and cultural norms, including "changing SRH priorities" and "changing marital prototype". Conclusion: In this study, men perceived SRH as an important issue due to the changes in social and cultural trends, and many of their SRH needs have not yet been addressed. Hence, along with socio-economic changes, the policymakers of the health system should develop strategies and interventions to meet these needs.